2001
DOI: 10.21273/hortsci.36.4.721
|View full text |Cite
|
Sign up to set email alerts
|

Paclobutrazol Soaked Marigold, Geranium, and Tomato Seeds Produce Short Seedlings

Abstract: Bedding plants and many vegetable crop seeds are often sown in plug trays. Some crops, like marigold (Tagetes sp. L.), tend to stretch early after germination, especially if grown in low light environments. By the time growers apply plant growth regulators (PGRs), stretching of the hypocotyl has already occurred and seedling applications are ineffective. Seedling height may be controlled by applying the plant growth regulator directly to the seed. Seeds of `Bonanza Gold' mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 6 publications
1
32
2
Order By: Relevance
“…They speculated that PB adhered to the seedcoat was released into the blotter paper reaching concentrations which inhibited germination. While Pasian and Bennett (2001) found that germination in the lab was inhibited as PB concentration and soaking time increased, in the current study, neither PB concentration nor soaking time affected germination of 'Better Boy' tomato. This is similar to the findings of Groot and Karssen (1987) and Still and Pill (2003).…”
Section: Resultscontrasting
confidence: 82%
See 3 more Smart Citations
“…They speculated that PB adhered to the seedcoat was released into the blotter paper reaching concentrations which inhibited germination. While Pasian and Bennett (2001) found that germination in the lab was inhibited as PB concentration and soaking time increased, in the current study, neither PB concentration nor soaking time affected germination of 'Better Boy' tomato. This is similar to the findings of Groot and Karssen (1987) and Still and Pill (2003).…”
Section: Resultscontrasting
confidence: 82%
“…They concluded that in this species, newly synthesized GAs are responsible for germination. In tomato, Pasian and Bennett (2001) found that 500 to 1000 mg PB/L inhibited germination when seeds were germinated on blotter paper. They speculated that PB adhered to the seedcoat was released into the blotter paper reaching concentrations which inhibited germination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systemic properties of paclobutrazol and other triazoles have been shown to allow the application of growth retardants to seeds with either minimal or no effect on seed germination (Pasian and Bennett, 2001). Triazoles inhibit monooxygenases, which oxidase in three steps ent-kaurene to ent-kaurenoic acid, an early reaction in GA biosynthesis (Rademacher, 2000).…”
Section: Introductionmentioning
confidence: 99%